2020
DOI: 10.1111/ijpo.12604
|View full text |Cite
|
Sign up to set email alerts
|

Lean mass index is positively associated with white matter volumes in several brain regions in children with overweight/obesity

Abstract: Summary Background The relationship of obesity with grey and white matter volumes has been examined in several studies, and the results are decidedly mixed. Objective To investigate the associations of body mass index (BMI), fat mass index (FMI) and lean mass index (LMI) with total and regional grey and white matter volumes. Methods This is a cross‐sectional study involving 100 children (60% boys) with overweight/obesity. T1‐weighted images were acquired using magnetic resonance imaging. Dual energy X‐ray abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 52 publications
0
13
1
Order By: Relevance
“…Of note, MUO had higher BMI than MHO in this study, which could explain a potential relationship of higher body size with larger brain volumes. However, the difference between groups was small (around 2 km/m 2 ) and BMI did not show associations with gray matter volume in this sample in a previous study [9]. Thus, its confounding effect in this study associations does not appear to be relevant.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Of note, MUO had higher BMI than MHO in this study, which could explain a potential relationship of higher body size with larger brain volumes. However, the difference between groups was small (around 2 km/m 2 ) and BMI did not show associations with gray matter volume in this sample in a previous study [9]. Thus, its confounding effect in this study associations does not appear to be relevant.…”
Section: Discussioncontrasting
confidence: 66%
“…In the last few years, an increased body of evidence has emerged on obesity-related comorbidities and metabolic alterations and their relationship with structural brain abnormalities in children and adolescents [9,[34][35][36]. For instance, Perlaki et al [36] showed that a higher degree of obesity was associated with greater volumes in the amygdala and accumbens, regions involved in the food rewards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with overweight/obesity have been characterized as having poorer sleep behaviors, [25][26][27] and smaller GMV than children with a normal weight. [28][29][30] Furthermore, these children often engage in greater sedentary time (SED) and insufficient physical activity, 31 which may also be associated with poorer sleep behaviors. 32,33 SED and physical activity behaviors coexist with sleep in the 24-hour cycle.…”
mentioning
confidence: 99%
“…Additionally, MRI evidence suggests that lean mass index (LMI) among children with overweight or OB is positively associated with regions overlapping white matter tracts, which are related to executive function and planning, emotion and conflict processing, visual processing, attention, memory, and motor function, independent of fat mass index or BMI 43. These data contribute to previously mixed findings in the field of OB with grey and white matter, such that LMI…”
mentioning
confidence: 53%